Identifying Morphological Patterns of Hippocampal Atrophy in Patients With Mesial Temporal Lobe Epilepsy and Alzheimer Disease - Duan, Yiran; Lin, Yicong; Rosen, Dennis; Du, Jialin; He, Liu; Wang, Yuping (Frontiers in Neurology, 2020)
Purpose Mesial temporal lobe epilepsy (MTLE) and Alzheimer's disease (AD) are two distinct neurological disorders associated with hippocampal atrophy. Our goal is to analyze the morphologic patterns of hippocampal atrophy to better understand the underlying pathological and clinical characteristics of the two conditions. Methods Twenty-five patients with AD and 20 healthy controls with matched age and gender were recruited into the AD group. Twenty-three MTLE patients and 28 healthy controls with matched age and gender were recruited into the MTLE group. All subjects were scanned on 3T-MRI scanner. Automated volumetric analysis was applied to measure and compare the hippocampal volume of the two respective groups. Vertex-based morphologic analysis was applied to characterize the morphology patterns of hippocampal atrophy within and between groups, and a correlation analysis was performed. Results Volumetric analysis revealed significantly decreased hippocampal volume in both AD and MTLE patients compared to the controls. In the patients with AD, the mean total hippocampal volume was 32.70% smaller than that of healthy controls, without a significant difference between the left and the right hippocampus (p < 0.05). In patients with MTLE, a significant reduction in unilateral hippocampal volume was observed, with a mean volume reduction of 28.38% as compared with healthy controls (p < 0.05). Vertex-based morphologic analysis revealed a generalized shrinkage of the hippocampi in AD patients, especially in the bilateral medial and lateral regions. In MTLE group, atrophy was only seen in the an ipsilateral head, ipsilateral lateral body and slightly contralateral tailterior portion of the unilateral hippocampus (FWE-corrected, p < 0.05). Conclusions MTLE and AD have distinctive morphologic patterns of hippocampal atrophy, which provide a new insight into the radiology-pathology correlation in these diseases.